Petrological study of the Cotacachi-Cuicocha Volcanic Complex, Ecuador: understanding the eruptive dynamic and evolution of the magma - García Paredes, Evelyn Raquel (2020)
Ecuador is a country with 97 volcanoes, of which 13 are considered as active. Therefore, volcanic hazards are an important and concerning issue for Ecuadorians and their authorities. Most of these volcanoes are stratovolcanoes which usually present a complex and varied eruptive history. One of this, is the dormant Cotacachi volcano, which is part of the Cotacachi-Cuicocha Volcanic Complex (CCVC). This volcanic complex is located in the Western Cordillera of Ecuador and comprises, apart from the Cotacachi volcano, three satellite domes called Peribuela, Loma Negra and Muyurcu, and the Cuicocha caldera, which have four intra-caldera domes. The latest activity recorded of this volcanic complex was located on the southern flank of the Cotacachi volcano, with the growth of a fourth dome, destroyed in a caldera-forming eruption ~3.1 ka ago, and the growth of the four intra-caldera domes. In this thesis, data from a petrological study, which includes the use of an optical microscope and SEM coupled with an EDS detector, is presented, with an emphasis on the analysis of textures, chemical zonation, reaction rims in crystals and physical properties of the rocks from the CCVC. Textures such as oscillatory zoning, patchy zones, and sieve textures found in plagioclase crystals indicate kinetic effects and long-term processes within the magmatic chamber, decompression in magmas undersaturated in water, and magma mixing, respectively. Chemical zonation in pyroxene crystals shows different magma composition, and reaction rims in amphibole crystals reveal heating or decompression-induced processes that occurred during rim growth. Furthermore, the crystal population, their modal abundance, and vesicles were analyzed and related to viscosity. By considering all these data, we recognize some magmatic processes that occurred throughout the history of the CCVC, and we were able to reconstruct the magmatic history of the different eruptive phases of this volcanic complex.